The Role of Geographers in the Field of Health (A Health Study with a Geographical Approach) - Salakory, Melianus (GEOFORUM, 2023)
The book "Geography of Health: Applications of Science and Learning" contains ideas, thoughts, concepts, and several research findings that, when integrated and implemented, have given birth to and justified the emergence of health geography, which has so far developed only at the level of academic discussion. This book was created amidst the spread of the COVID-19 pandemic, which has had a domino effect globally, impacting individuals, groups, and nations alike. The method used in the book is a book review. This review includes a synopsis, a brief overview of the book with citations, an analysis of the book's strengths and weaknesses, and recommendations. "Geography of Health: Applications of Science and Learning" consists of six chapters. The introductory section discusses the concept of geography as a study of the geosphere, introduces the Maluku region as an archipelago with a predominance of small islands, addresses the issues of small islands and the urgency of solving them, discusses the position of health geography in the curriculum of the Geography Education Program at the Faculty of Teacher Training and Education (FKIP) at Pattimura University, and explores the application of geographical science and learning in the health field with two research studies related to environment-associated diseases (Soil-Transmitted Helminths and Early Warning for Malaria Outbreaks).